Genotyping of Salmonella Typhi using 8-loci multi locus VNTR analysis. Issue 1 (December 2016) - Wang, Hongxia; Diao, Baowei; Cui, Zhigang; Yan, Meiying; Kan, Biao
Abstract Background Typhoid fever has caused severe epidemics in many Asian and African countries. The early detection of outbreaks and their sources may promote the prevention and control of typhoid fever, for which effective and timely molecular subtyping techniques are required. Pulsed field gel electrophoresis (PFGE) is routinely used as the molecular typing technique for foodborne and waterborne pathogens. However, maneuverable techniques remain necessary to expedite the experimental procedure and obtain more effective subtyping. The multilocus loci of a variable number of tandem repeats (VNTR) analysis (MLVA) is a polymerase chain reaction (PCR)-based subtyping method. Methods MLVA method and PFGE based onXba I enzyme were applied to the 103Salmonella Typhi (S . Typhi) isolated from different years and regions. Dendrograms were constructed and analyzed to help understand the data. The Simpson's index of diversity (D value) was calculated to estimate the discriminatory power of MLVA and PFGE. In addition, a set of endogenous 3 bp DNA ladder markers were established to accurately determine the repeat copy number of the VNTR with only a 3 bp repetitive unit, using microfluidics chip-based electrophoresis to generate comparable VNTR data in the public health laboratory network. Results The established 8-loci MLVA forS . Typhi subtyping had higher discriminatory power than PFGE. In some cases, PFGE could not distinguish the strains isolated over long intervals and with different epidemic provinces. By contrast, 8-loci MLVA distinctly distinguished these strains, and the strains with the same MLVA patterns were from the same or contiguous years and the same province, showing its significance in epidemiological discrimination. The established set of endogenous 3 bp DNA ladder markers improved the accuracy and reproducibility of VNTR analysis using microfluidics chip-based electrophoresis to 100 %. Conclusions Eight VNTRs can be used for the MLVA analysis of the 103S . Typhi isolates. MLVA based on the 8-loci had higher discriminatory power than PFGE forS . Typhi subtyping. The 8-loci MLVA is easier for the analysis and interpretation of relationships between strains compared to PFGE.